2009
DOI: 10.1007/s11999-009-1039-8
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Recombinant Human BMP-2 for Treating Complex Tibial Plateau Fractures: A Preliminary Report

Abstract: Level IV, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
91
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(94 citation statements)
references
References 49 publications
3
91
0
Order By: Relevance
“…19e21 Unfortunately, the high BMP2 concentrations required for osteogenesis in humans are associated with significant adverse effects, including an FDA warning of life-threatening cervical swelling, 22 ectopic bone formation (U.S. Food and Drug Administration, http://www.fda. gov/MedicalDevices/Safety/AlertsandNotices/PublicHealth Notifications/ucm062000.htm, last accessed September 28, 2011), 23 osteoclastogenesis, 24 and inconsistent bone formation. 25 Thus, improving the safety and efficacy of BMP2-based skeletal repair is crucial.…”
mentioning
confidence: 99%
“…19e21 Unfortunately, the high BMP2 concentrations required for osteogenesis in humans are associated with significant adverse effects, including an FDA warning of life-threatening cervical swelling, 22 ectopic bone formation (U.S. Food and Drug Administration, http://www.fda. gov/MedicalDevices/Safety/AlertsandNotices/PublicHealth Notifications/ucm062000.htm, last accessed September 28, 2011), 23 osteoclastogenesis, 24 and inconsistent bone formation. 25 Thus, improving the safety and efficacy of BMP2-based skeletal repair is crucial.…”
mentioning
confidence: 99%
“…[11][12][13] However, the introduction of growth factors to a system for use in the craniofacial region carries risks of tissue overgrowth, nerve impingement, and additional regulatory challenges. 14 To that effect, strategies utilizing in vivo bioreactors without exogenous growth factors are being explored. Specifically, poly(methyl methacrylate) (PMMA)-based chambers have been filled with different scaffold materials and implanted against the periosteum of sheep rib for tissue generation.…”
mentioning
confidence: 99%
“…Moreover, they showed to be a valid approach in combination with allografts, as an alternative to ABG, leading to the same beneficial effects but avoiding the drawbacks related to invasive autologous bone harvesting procedures [23]. The negative results reported were related to the higher rate of complications in the rhBMPs group, i.e., heterotopic ossification or calcification [25,30], local oedema, or calcinosis [30].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the potential adverse events of BMPs, this systematic review on the treatment of bone fractures, non union, and osteonecrosis, also focused on the literature evidence of complications related to these orthopaedic conditions. The analysis of the comparative studies underlining a higher percentage of complications, showed that the majority of complications after BMPs treatment were related to heterotopic ossification, which were reported in 3 papers on fracture repair [25,29,34], in 2 papers on non union treatment [40,44], and in 1 paper on osteonecrosis [59] involving both rhBMP-2 and 7. Moreover, other described complications were infections [26,55], peripheral oedema, heterotopic ossification/soft-tissues calcification, new or increased pain [26], and the development of distal tibiofibular synostosis (1/52) described with rhBMP-7 for non-union treatment [52].…”
Section: Complicationsmentioning
confidence: 99%